PROBLEMS OF THE ACCOUNTING BUSINESS ANALYSIS OF THE STRATEGY OF THE COMPANY IN A BALANCED SYSTEM OF INDICATORS - Timchev, Marko Lyubomirov (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
In the scientific report opportunities for integration of accounting business analysis into a balanced scorecard have been explored and a concentric model has been proposed. The report proposes a methodology, models and indicators for analyzing the financial strategy of the corporation. Models, methods and indicators for analysis of the business strategy, financial and operational risk of the companies have been proposed.